Arte de ser mulher: prevenção e enfrentamento da violência doméstica na perspectiva interdisciplinar - Ferreira, Carolina Silvestre [UNESP]; Palone, Luana Caroline Furriel [UNESP]; Brasileiro, Lorena Carpinelli Perozzi [UNESP]; Vargas, Narayana Teixeira [UNESP]; Canavez, Luciana Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Art of being a woman: prevention and fighting domestic violence in interdisciplinary perspective", is an extension project of Auxiliary Unit Social Cool Center of UNESP in Franca/SP, Brazil. It aims to clarify Franca's society about law 11.340/06 (Maria da Penha Law) and study domestic violence suffered by women in the city, with the main purpose to raise awareness and educate this society for preventive action and show the dimension of the problematic discussed, showing ways of how to face them.

“Arte de ser mulher: prevenção e enfrentamento da violência doméstica na perspectiva interdisciplinar”, é um projeto de extensão da Unidade Auxiliar Centro Jurídico Social da UNESP Franca/SP. Objetiva esclarecer a sociedade francana acerca da lei 11.340/06 (Lei Maria da Penha) e estudar a violência doméstica sofrida por mulheres na cidade, tendo como principal finalidade sensibilizar e conscientizar essa sociedade para uma ação preventiva e apresentar a dimensão da problemática discutida, mostrando assim maneiras de enfrentá-la.
Keywords: Against women; Law; Community-institution relationship; Violência contra a mulher; Lei; Relação comunidade-instituição